The Relationship Between Patient Characteristics Diabetes Self-Care Management with Diabetic Peripheral Neuropathy in Type 2 DM Patients in Regional General Hospital in Indonesia (International Journal of Nursing Education, 2022)
One of the microvascular complications is loss of sensation in the leg area (peripheral neuropathy) which causesfoot ulcers and the risk of amputation. The purpose of this study was to determine the relationship betweenpatient characteristics and Diabetes Self-Care Management (DSCM) with Diabetic Peripheral Neuropathy (DPN)in type 2 diabetes mellitus patients in a regional public hospital in one of the provinces in Indonesia. This studyused a correlative design with a cross-sectional approach to 154 patients with type 2 diabetes mellitus who wereselected using a proportionate stratified random sampling technique. The data were obtained using a Summaryof Diabetes Self-Care Activities and the Michigan Diabetic Neuropathy Score and analyzed using the Chi-squaretest and logistic regression. The results showed that age and duration of diabetes were the sub-variables ofpatient characteristics that were most associated with neuropathy in diabetic patients. Patients are expectedto be able to do diabetes management regularly so that no more diabetes patients are injured due to a lack ofself-management. Hospitals are expected to routinely carry out training and counseling for diabetic patients toprevent serious complications caused by peripheral neuropathy.